A chemical examination of certain baking powders - Dalton, Winifred Anna (My University, 1906)
Introduction: The necessity of having bread preparations raised quickly for immediate baking led to the use of chemical agents for that purpose. In all of these agents the gas, which expands, is obtained by the decomposition of a carbonate which is introduced with an acid constituent to act upon it, directly in the flour. When water is added to the flour to make the dough, the chemicals are dissolved and the action takes place, carbon dioxide and water being formed, the carbon dioxide acting as the expansive gas. Many people suppose that nothing remains in the bread from that reaction, that it is all driven off during the baking. There is a residue left which varies with the different powders, and is more or less objectionable depending on the powder used. There are some combinations which leave a minimum amount of residue and of the least objectionable character, while others are the reverse. Most people do not know the healthful character of some of these combinations used and do not realize the danger of using cheap baking-powders when used to any great extent. The essential constituents of a good baking-powder are first; a carbonate or bicarbonate of an alkali metal and, second; an acid constituent capable of combining with the alkali metal forming a salt, and liberating the carbon dioxide. For the alkaline constituent, sodium bicarbonate is chiefly used, though sometimes ammonium bicarbonate (acid ammonium carbonate) is substituted for it. For the acid constituent various substances are used. Potassium bitartrate, free tartaric acid, an acid phosphate, or an alum, are the most common ones. The acid and alkaline constituents are about in the proper proportions for combination, and starch or flour is added to them so they will not react in the dry state but may be kept indefinitely. Baking powders may be classified into three classes: 1. Tartrate powders, in which the acid constituent is potassium bitartrate or free tartaric acid. 2. Phosphate powders, in which the acid constituent is an acid phosphate. 3. Alum powders, in which the acid constituent is an alum. Many powders are combinations of two of these classes.
Citation: Dalton, Winifred Anna. A chemical examination of certain baking powders. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Chemistry; Baking Powder; Baking; Bread; Tartrate; Phosphate; Alum; Theses